Analisis Mitra Utama Dan Aktivitas Utama dalam Model (BMC) pada Usaha Dodol Monas Jaya di Kelurahan Allepolea Kecamatan Lau Kabupaten Maros - Syahrini Afriani; Azisah Azisah; Mohammad Anwar Sadat (Jurnal Agribis, 2026)
This study aims to analyze the business model of the dodol business in Maros using the Business Model Canvas (BMC) approach. By adopting the BMC, this study explores key elements such as customer segments, value propositions, distribution channels, customer relationships, key resources, key activities, key partners, and cost structures and revenue streams. This research method involved in-depth interviews with dodol business owners and direct observation of the manufacturing process using the Business Model Canvas (BMC). The analysis shows that the dodol business in Maros has a competitive value proposition through the use of high-quality local raw materials and unique flavor innovations. Effective distribution channels are utilized. Customer relationships are built through good service, thus fostering customer loyalty. This study concludes that utilizing the Business Model Canvas (BMC) as a strategic tool can help dodol entrepreneurs formulate more targeted strategies to increase competitiveness and business sustainability in the local souvenir market.